An Opinion about the Current Development and Immunity of Zika Vaccines - Ibrahim M S Shnawa (Journal of Global Pharma Technology, 2019)
The current available developing zika virus vaccines and virus immunity are being stated. All the known vaccine classes have been attempted for evolving human zika approved vaccine(s).At the experimental preclinical level both preventive and therapeutic vaccines are known. While on clinical level, neither preventive nor therapeutic zika vaccines are globally approved for public human use till now. Zika vaccine immunity in mice monkeys and to lesser extent in man has shown to be dependent on the nature of the active immunogen forming the investigational vaccine. Different vaccine design may affect different immune response types. The vaccine immunity in mice and monkeys are rather different from that of man though they are of mammalian lineage. Live attenuated and inactivated whole virus vaccines induced virus neutralizing zika antibody responses .Zika DNA vaccine makes induced cell mediated immunity .mRNA vaccines showed antibody and cell mediated immunity. The features of zika infection versus zika vaccine immunity can be summarized as :i- Virus neutralizing antibody responses ,ii-antibody response reduces local and systemic viremia associated with immune protection ,iii- post challenge sterile immunity ,iv- antibody dependent immune enhancement of other related viruses ,v-zika pathologic autoantibody mediate nervous immune tissue injuries ,and v-zika specific monoclonal antibodies were found valid for immunotherapy of zika infection based onto passive immune effect of mAb at the experimental level. Having an in hand global approved zika vaccine will needs around five to ten years to be attained.Keywords: Antibody, Autoantibody